Incorporation of jassid, amrasca biguttula biguttula (Ishida) resistance in a bacterial wilt resistant background in brinjal. - Seeshma K S (Department of Olericulture, College of Horticulture, 2011)
Brinjal or egg plant (Solanum melongena L.) is one of the most important vegetable crops of India for which the country occupies second position in production. In the country crop is grown in an area of 6.12 lakh hectares producing 105.63 lakh tonnes with an average productivity of 17.26 tonnes per hectare (NHB database, 2010). During summer, the cultivation of brinjal is limited in Kerala due to the severe incidence of sucking insects, especially jassids (Amrasca biguttula biguttula) which are causing severe yield reduction in brinjal. Malini (2005) screened 36 accessions of brinjal to identify the sources of resistance to jassid attack and she reported seven brinjal genotypes with jassid resistance. The proposed study was conducted to transfer this jassid resistance from four identified sources (SM 363, SM 364, SM 366, and SM 385) into the bacterial wilt resistant commercial varieties like Surya, Swetha and Haritha through hybridization. These seven parents were raised in the pots and the bacterial wilt resistant varieties were crossed directly with jassid resistant accessions to develop 12 F1hybrids. The resulting 12 F1 hybrids along with seven parents were raised in the field as well as in sterilized pots. The crop was raised in the field in randomized block design with two replications. The plot size was 5.4 m2 with 12 plants in each replication planted at a distance of 0.75 x 0.60 m. The performance of the accessions was studied and they were screened for jassid and bacterial wilt resistance. The experiments were conducted during kharif (2010) and summer (2011). The biometrical characters were recorded and genetic parameters of 19 brinjal accessions were estimated. The results showed that all accessions had significant difference for most of the characters studied among which Surya x SM 366 and Surya x SM 385 were found to have good yield characters. In the case of earliness, Surya x SM 366 and Haritha x SM 366 were found to be better hybrids. The heterotic study revealed that among the F1 hybrids, Surya x SM 366 and Haritha x SM 366 were having high and significant standard heterosis for earliness to flowering and fruiting from the standard variety Haritha. For yield characteristics, Surya x SM 366 was found to be best hybrid with maximum and significant heterosis from better parent, standard variety and mid parent. The estimates of combining ability analysis revealed that the male parent SM 366 was the best general combiner for most of the characters like plant height, days to first flowering, days to first harvest, number of economic harvests, yield per plant and yield per plot. In the case of specific combining ability, Swetha x SM 364 was found to be good specific combiner for yield characteristics. After the field screening and cage study for jassid resistance, two brinjal accessions viz. SM 363 and SM 366 were identified as highly resistant. Among the 12 F1 hybrids, Surya x SM 364, Surya x SM 385, Haritha x SM 364 and Haritha x SM 366 were moderately resistant. All other hybrids and the parents like Swetha and Haritha were grouped into susceptible category after the screening for jassid resistance. Screening for bacterial wilt resistance was also carried out to find out the hybrids with combined resistance to jassid and bacterial wilt. The accessions were categorized into either highly resistant or moderately resistant category after the field screening for bacterial wilt resistance. The F1 hybrids like Surya x SM 385 and Haritha x SM 366 were identified as better hybrids with combined resistance to jassids and bacterial wilt and with good yield characteristics. The study of leaf morphology of parents and F1 hybrids to unravel the mechanism of jassid resistance revealed that density of midrib hairs had a significant role in conferring resistance to jassids in brinjal whereas the leaf thickness and midrib thickness did not show any significant difference among resistant and susceptible accessions.